IMPOLITENESS STRATEGIES IN PETER RABBIT MOVIE - Indah Permata Sari; Nuri Emmiyati; Sardian Maharani Asnur (Elite : English and Literature Journal, 2019)
This thesis is about impoliteness strategies in Peter Rabbit movie. It aims to find out the impoliteness strategies and the response of interlocutors in the movie. This study used the theory of Culpeper (1996) about the 5 strategies of impoliteness and Culpeper, et.al (2003) 4 types of impoliteness responses. The researcher utilised descriptive qualitative method to analyze the data and to describe the results of this analysis. The source of the data is Peter Rabbit movie and the script of the movie. From read, watch, check the accuracy between the movie and the script, identify characters’ utterances, identify the impoliteness strategies of the utterances and identify the response of the impoliteness are the procedures of data collection. The results of this study indicate that there are 75 impoliteness strategies used by the characters in Peter Rabbit movie. The most commonly strategy used is Bald on Record strategy with total usage of 30 times. Meanwhile, Positive Impoliteness and Sarcasm or Mock Politeness were used 15 times Total usage of Negative Impoliteness is 12 times. The most rarely strategy found is Withhold Politeness with the number of usage 4 times. The response found consisted of 4 types of responses namely Accepting face attack, Offensive Countering, Defensive Countering, and No response whether it is in the form of verbal and nonverbal responses. This analysis shows that the Impoliteness Strategy in Peter Rabbit movie is quite a lot because the characteristic of the characters in the movie is classified as aggressive and active. In addition, the use of impoliteness strategies was influenced by different cultural backgrounds such as urban people and country people.ABSTRAKPenelitian ini tentang strategi ketidaksopanan di dalam film Peter Rabbit. Penelitian ini bertujuan untuk menemukan stratgei ketidaksopanan dan respons lawan bicara yang ada di dalam film. Penelitian ini menggunakan teori Culpeper (1996) tentang 5 strategi ketidaksopanan dan teori Culpeper dan temannya (2003) tentang 4 tipe respon ketidaksopanan. Peneliti menggunakan metode kualitatif untuk menganalisa data dan mendeskripsikan hasil dari analisis ini. Sumber data berupa film dan skrip dari Peter Rabbit. Dari membaca, menonton, mengecek keakuratan  film da skrip, mengidentifikasi percakapan-percaakapan para karakter, mengidentifikasi strategi ketidaksopanan pada percakapan  para karakter  dan mengidentifikasi respon dari pendengar merupakan prosedur dari data yang dikumpulkan. Hasil dari penelitian ini menunjukkan bahwa strategi yang paling sering di gunakan adalah strategi Bald on Record  dengan jumlah penggunaannya 30 kali. Sementara itu, Positive Impoliteness dan Sarcasm or Mock Politeness di gunakan 15 kali. Jumlah penggunaan  Negative impoliteness 12 kali. Strategi yang paling jarang di temukan adalah Withold Politeness dengan total penggunaannya 4 kali. Respons yang di temukan terdiri dari 4 tipe respons yakni Accepting face attack, Offensive Countering, Defensive Countering, and No response baik dari segi  respon verbal dan non verbal. Penelitian ini menunjukkan bahwa strategi ketidaksopanan di dalam film Peter Rabbit cukup banyak karena sifat para karakter  di dalam film agresif dan aktif. Selain itu, penggunaan ketidaksopanan di pengaruhi oleh perbedaan latar belakang budaya seperti orang dari perkotaan dan orang dari pedesaan.Kata Kunci: Pragmatik, Strategi, Strategi Ketidaksopanan, Respons, Peter Rabbit